2020
DOI: 10.1108/afr-05-2020-0072
|View full text |Cite
|
Sign up to set email alerts
|

Flexible loans and access to agricultural credit for smallholder farmers in Kenya

Abstract: PurposeThe purpose of this paper is to determine the level of flexibility in loan products offered to smallholder farmers in Siaya County in Kenya and to examine the effect of flexibility on access to credit.Design/methodology/approachThe paper uses primary survey data from a sample of smallholder farmers in Siaya County in Kenya who had borrowed from various lending institutions within the study area. The paper develops an index variable of loan flexibility using multiple correspondence analysis (MCA) techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…The study by Ahmed et al (2000), for example, highlights that changes in management technologies have a direct impact on household income patterns of food and non-food expenditure and caloric intake of the families involved. However, the utilization of appropriate strategies and techniques is constrained by the limited availability of financing (Odhiambo and Upadhyaya, 2020). While limited literature exists on the ways in which flexibility can improve access to financing, it does not highlight how the financing facility can be structured around traditional and prevalent practices that are widely accepted and would therefore be easier to emulate by means of simple formalization.…”
Section: The Financial Viability Of Adhyaramentioning
confidence: 99%
“…The study by Ahmed et al (2000), for example, highlights that changes in management technologies have a direct impact on household income patterns of food and non-food expenditure and caloric intake of the families involved. However, the utilization of appropriate strategies and techniques is constrained by the limited availability of financing (Odhiambo and Upadhyaya, 2020). While limited literature exists on the ways in which flexibility can improve access to financing, it does not highlight how the financing facility can be structured around traditional and prevalent practices that are widely accepted and would therefore be easier to emulate by means of simple formalization.…”
Section: The Financial Viability Of Adhyaramentioning
confidence: 99%
“…Ullah et al [13,14] reported that access to agricultural loans from banks enabled smallholder farmers to adopt and use novel agricultural technologies in farming. Odhiambo [6] also found that farmers who got flexible loans from government agencies were able to buy and use improved inputs such as seeds, fertilizers, and pesticides.…”
Section: Sources Of Agricultural Credit and Correlationmentioning
confidence: 99%
“…The results supported the findings of Zulfiqar [27] that the rate of the farmers' access to agricultural credit is low. However, it opposed Odhiambo [6] that a larger percentage of smallholder farmers are increasingly accessing agricultural loans.…”
Section: Level Of Access To Agricultural Creditmentioning
confidence: 99%
See 1 more Smart Citation